2021
DOI: 10.1007/s00449-021-02659-8
|View full text |Cite
|
Sign up to set email alerts
|

Rice straw enhancing catalysis of Pseudomonas fluorescens lipase for synthesis of citronellyl acetate

Abstract: Citronellyl acetate as an important flavor, can be effectively synthesized by lipase catalysis in nonaqueous system. But lipases usually behave low catalytic activity due to aggregation and denaturation of them in organic phase. To enhance the nonaqueous catalysis, based on the mechanism of lipases activated at water/oil (organic phase) interface, the inexpensive race straw was processed into powder and filaments on which Pseudomonas fluorescens lipase was immobilized by physical adsorption, used for synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Therefore, the effect of acetaldehyde on immobilized PFL can be ignored during reuse. Rice straw was processed into powder and filaments, on which PFL was immobilized (RSD-PFL and RSF-PFL) for a transesterification reaction to produce citronellyl acetate in a solvent-free system [28]. The highest yield reached 96%.…”
Section: Operational Stability Of Immobilized Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effect of acetaldehyde on immobilized PFL can be ignored during reuse. Rice straw was processed into powder and filaments, on which PFL was immobilized (RSD-PFL and RSF-PFL) for a transesterification reaction to produce citronellyl acetate in a solvent-free system [28]. The highest yield reached 96%.…”
Section: Operational Stability Of Immobilized Enzymementioning
confidence: 99%
“…Lipase-catalyzed transesterification for citronellyl acetate is a typical green and environmentally friendly process, with the advantages of mild reaction conditions, high catalytic efficiency, and strong catalytic specificity. For its production, inexpensive raceme straw was processed into powder and filaments, on which Pseudomonas fluorescens lipase was immobilized by physical adsorption to synthesize citronellyl acetate via transesterification of citronellol and vinyl acetate [28]. The results showed that 99.8% conversion could be achieved after 12 h at 37 • C and 160 rpm.…”
Section: Introductionmentioning
confidence: 99%
“…Jian XIONG 1# * , Wenyuan SUN 1# , Hanghang XU 1 , Jinhui BIAN 2 , Yafei SONG 1 , Shengwei PAN 1 , Jiayu GAO 1 At present, there are few reports about the lipase-catalyzed synthesis of citronellyl acetate in non-aqueous solvents. Yuan et al (2022) based on the activation mechanism of lipase at the water/oil (organic phase) interface, inexpensive raceme straw was processed into powder and filaments on which Pseudomonas fluorescens lipase was immobilised by physical adsorption to synthesise citronellol via ester exchange of citronellol and vinyl acetate. The results showed that 99.8% conversion could be achieved after 12 hours at 37 °C and 160 r/min.…”
Section: Synthesis Of Citronella Acetate By Lipase Catalyzed Transest...mentioning
confidence: 99%